Evaluasi Usability Website Shopee Menggunakan System Usability Scale (SUS) - Firman Galuh Sembodo; Gita Fadila Fitriana; Novian Adi Prasetyo (Politeknik Negeri Batam, 2021)
The progress of information technology is currently growing rapidly. Technology related to the internet is often a solution to most of the problems in existing needs, especially those related to the effectiveness and efficiency of activities and procedures. In this final project, the author discusses websites in the business field, namely e-commerce websites. In this study, the authors chose one of the most popular e-commerce websites in Indonesia this year, namely the shopee website, a website that not only offers products but also puts forward the appearance of the Shopee website which must always be considered because it is the main factor to increase customer purchases. In this study, the quality of the web that will be measured by users, especially for consumers, is based on measuring the quality of the website using the System Usability Scale (SUS). Evaluation of the shopee website is the first step to measure the level of usability on the website. Usability evaluation on the website is carried out to collect opinions from various respondents regarding the functionality of the website. In this study, the results obtained from the calculation of the average usability of the shopee website of 67.08 so that it can be said that the usability of the shopee website on product purchases has entered the OK category.